Inter and intra-specific diversity in Alternaria species infecting oilseed Brassicas in India (Journal of Oilseed Brassica, 2026)
The work was initiated to determine diversity in pathogen population of Alternaria blight which results in up to 60% yield losses in the world. It is a most prevalent fungal disease of oilseed Brassica in North and North- West regions of India where approximately 80% of Brassicas are grown. Fifty five single spore isolates of Alternaria species (32 of A. brassicae, 20 of A. brassicicola and 3 of A. alternata) were isolated from infected leaf samples collected from 8 states of India. The purified isolates were evaluated for their morphological, cultural, biochemical and molecular characteristics, and also preserved in DMSO and glycerol. Significant variations (P< 0.05) were observed in sporulation intensity, spore morphology, radial growth and carbohydrate concentration among isolates of each species. Analysis of RAPD banding profiles also showed a high level of genetic diversity varying between 57-78%, 78-92% and 89-100%, among the A. brassicae, A. brassicicola and A. alternata isolates, respectively. Extensive variations were observed in isolates for all the parameters studied, but no correlation could be established. This study, thus indicates that a significant non-specific variation exist between isolates infecting different species and varieties of Brassica in India. This is the first report of comparative evaluation of the three Alternaria species from different locations, on three different media and cryopreservation.